The Effect of Bronchial Asthma on Interatrial Electromechanical Delay Coupling Obtained Using Tissue Doppler Imaging - Yazdan Ghandi; Danial Habibi; Mohammad Abasi (Iranian Journal of Medical Sciences, 2019)
Background: Asthma is a predisposing factor for the development of atrial ﬁbrillation. Asthma disturbs the electrophysiology in the right and left atrium. The aim of this study was to evaluate atrial electromechanical delay by coupling obtained from tissue Doppler imaging (TDI) in children. Methods: A cross-sectional study was conducted on 50 patients with Bronchial Asthma, compared with 50 healthy children. The intra-right atrial conduction time (IRCT), intra-left atrial conduction time (ILCT), and interatrial conduction time (IACT) were calculated. The function of systolic and diastolic right ventricular (RV) was assessed by TDI, conventional echocardiography, and pulse Doppler wave. The pulmonary function test was carried out for all the subjects by spirometry. We used an independent Student’s t test and Pearson’s correlation test for analyzing the data.Results: The findings revealed normal shape in both atrial between the two groups. The diastolic RV function was not significantly different between the subjects as measured by the pulse wave Doppler in the tricuspid flow. Patients in the experimental group had signiﬁcantly higher intra and interatrial electromechanical delays (P=0.007) than the control group. This difference was statistically signiﬁcant with regard to IRCT (P=0.0001) and IACT (P=0.005). IRCT/IACT and myocardia performance index (r=0.35, P=0.004; and r=0.52, P=0.008) correlated with isovolumetric relaxation time (r=0.46, P=0.003; and r=0.58, P=0.008).Conclusion: We found that IRCT and IACT prolonged in pediatricswith asthma. Also, it was found that there was a correlation between IRCT and IACT, on one hand, and RV myocardial performance index, on the other hand, but they were not related to TDI diastolic parameters.